On the Potential of Dialogs in Advertising - Enrique Strelow; Katrin Talke; Mark Heitmann (Marketing Review St.Gallen, 2021)
In this paper, we argue and empirically show that the use of dialogs in advertisements can increase preference for the advertised brand. Dialogs should both facilitate ad content processing and appeal to consumers' dialogical self, thus enhancing affective brand response. We also show that the effect is amplified when dialogs are embedded in a story.
Keywords: 650